Uncertainty shocks and employment fluctuations in Germany: the role of establishment size - Kovalenko, Tim (Oxford Economic Papers, 2023)
Uncertainty shocks are found to affect labour market outcomes adversely. Most studies interrelate non-convex labour adjustment costs with the propagation of macroeconomic uncertainty to the labour market. I show that non-convex labour adjustment costs differ by establishment size in Germany. Hence, uncertainty shocks should affect large and small establishments differently. Therefore, this article studies the effects of uncertainty shocks on employment adjustments in large and small establishments employing four structural vector auto-regressive models for Germany from 1992 to 2014. These four models estimate the effects of uncertainty shocks on employment, worker flows, job flows, as well as worker churn in establishments with fewer than 100 and with at least 100 employees. The results suggest that uncertainty shocks trigger considerable employment fluctuations in large establishments while they barely affect small establishments. Furthermore, large establishments adjust their labour input by delaying the replacement of workers.
CRIS-Team WoS Importer:2023-05-12